Islamic Religious Education Teachers’ Strategies for Deaf Students at Taman Pendidikan Islam Special School - Vika Permata Sari; Mawaddah Nasution (UIN Sultan Aji Muhammad Idris Samarinda, 2026)
This study aims to explore the instructional strategies used by Islamic Religious Education (IRE) teachers in teaching deaf students at Taman Pendidikan Islam Special School. This study employed a qualitative descriptive approach to obtain an in-depth understanding of instructional strategies, learning approaches, and factors that support and hinder the learning process. Data were collected through observation, interviews, and documentation involving 1 principal, 1 IRE teachers, and 1 parent. The data analysis process adopted the interactive model of data reduction, data display, and conclusion drawing. The findings revealed that the instructional strategies applied by teachers primarily emphasized visual approaches, demonstrations, repetition, and direct practice. These strategies were considered effective in helping deaf students understand learning materials, particularly in mastering the practical aspects of Islamic teachings. However, several obstacles were identified, including limited teacher competence in sign language, inadequate special education backgrounds, insufficient learning facilities, and suboptimal lesson planning. On the other hand, supporting factors such as students’ learning motivation, positive teacher student relationships, and teacher commitment contributed positively to the learning process. Overall, this study concludes that although the instructional strategies used were appropriate to the characteristics of deaf students, improvements in teacher competence and educational facilities are still needed to achieve more effective learning outcomes. Keywords: deaf students, Islamic religious education, Learning strategies, Special education